A model system for in vitro studies of bank vole borne viruses. - Malin Stoltz (Public Library of Science (PLoS), 2011)
The bank vole (Myodes glareolus) is a common small mammal in Europe and a natural host for several important emerging zoonotic viruses, e.g. Puumala hantavirus (PUUV) that causes hemorrhagic fever with renal syndrome (HFRS). Hantaviruses are known to interfere with several signaling pathways in infected human cells, and HFRS is considered an immune-mediated disease. There is no in vitro-model available for infectious experiments in bank vole cells, nor tools for analyses of bank vole immune activation and responses. Consequently, it is not known if there are any differences in the regulation of virus induced responses in humans compared to natural hosts during infection. We here present an in vitro-model for studies of bank vole borne viruses and their interactions with natural host cell innate immune responses. Bank vole embryonic fibroblasts (VEFs) were isolated and shown to be susceptible for PUUV-infection, including a wild-type PUUV strain (only passaged in bank voles). The significance of VEFs as a model system for bank vole associated viruses was further established by infection studies showing that these cells are also susceptible to tick borne encephalitis, cowpox and Ljungan virus. The genes encoding bank vole IFN-β and Mx2 were partially sequenced and protocols for semi-quantitative RT-PCR were developed. Interestingly, PUUV did not induce an increased IFN-β or Mx2 mRNA expression. Corresponding infections with CPXV and LV induced IFN-β but not Mx2, while TBEV induced both IFN-β and Mx2. In conclusion, VEFs together with protocols developed for detection of bank vole innate immune activation provide valuable tools for future studies of how PUUV and other zoonotic viruses affect cells derived from bank voles compared to human cells. Notably, wild-type PUUV which has been difficult to cultivate in vitro readily infected VEFs, suggesting that embryonic fibroblasts from natural hosts might be valuable for isolation of wild-type hantaviruses.